MTconnect-based decision support system for local machine tool monitoring (2021)
Cyber-Physical Machine Tools (CPMT) are becoming ubiquitous parts of manufacturing sectors. CPMT offer immense potentials in the current CNC machine tool through integrating the machine tool and the machining process using computation and networking to enhance interconnection and autonomy. This study contributes to literature by presenting a variety of MTConnect applications in facilitating the decision making process at different production levels. We do this through addressing the challenges of data communication and management with CNC machine tool. Using the MTConnect protocol, we gathered near real-time data from a CNC machine. Next, the collected data are utilized to develop a local monitoring system that facilitates the decision-making process with applications on: i) production planning, ii) preventive maintenance, and iii) energy consumption analysis. In each application, various analyses and visualization techniques are presented to show the capabilities of the decision support system (DSS) for the operator. Finally, the advantages of the local DSS to improve the interoperability of the CNC through MTConnect are discussed.